Modelling the Flow of Knowledge and Human Capital: A Framework of Innovative Capital - d'Artis Kancs; Pavel Ciaian (Economics and Econometrics Research Institute (EERI), 2011)
Recently, the EU Council adopted a new labour migration policy instrument - the EU Blue Cards (BC) - for attracting the highly skilled workers to the EU. The present paper examines the potential impacts, which BC may cause on less developed sending countries (LDC). Our results suggest that the EU BC will reduce human capital in LDC. In addition, BC will also have a negative impact on knowledge capital. These findings suggest that without appropriate policy responses, BC makes developing country growth prospects rather bleak than blue. Therefore, we propose and analyse alternative migration policy instruments for LDC. We find that policies implemented on the demand side of the skilled labour market are the most efficient. In contrast, policies that address the supply side of the skilled labour market are the least efficient, though they might be less costly to implement.
Keywords: F02; F22; J24; J61; O15; 330; Knowledge capital; human capital; high-skill migration; innovative capital; economic growth